TRADITIONAL USE OF PLANTS AGAINST SNAKEBITE IN INDIAN SUBCONTINENT: A REVIEW OF THE RECENT LITERATURE - Dey, Abhijit; De, Jitendra Nath (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Snakebite has been a major cause of mortality across the tropical countries including Indian subcontinent. The present review deals with the enormous amount of ethnobotanical work performed in the last few years involving use of different plants against snakebite in Indian subcontinent (India, Bangladesh, Pakistan and Nepal). From a variety of literature sources the data has been compiled mentioning the plants, parts used, dosage, mode of administration, name of the ethnic communities, geographical locations etc. depending on the availability of information.